Modelo hidrogeológico do sistema aquífero Urucuia na bacia do rio Grande (BA) - Gonçalves, Roger Dias [UNESP]; Chang, Hung Kiang [UNESP] (My University, 2017)
The Urucuia Aquifer System represents a strategic water source in western Bahia. Its baseflow is responsible for the flow rate of the main tributaries of São Francisco river left bank in the dry season, including the Rio Grande, its main tributary in Bahia state. This work focuses on steady state numerical simulation using finite element method and computational algorithm FEFLOW. The numerical simulation results provided the conceptual model basis including a full free aquifer; null flux at plateau borders and aquifer base; hydraulic discrepancy from west to east and the hydraulic heterogeneity in the east side, performing 4 hydraulic conductivity zones varying between 1×10-5 m.s-1 to 5×10-4 m.s-1 and mean recharge rates varying approximately from 20% to 25% of average precipitation on recharge zones. The outflow calculated from water balance simulation is 2,37 × 107m³.day-1. The study attests the great contribution of Urucuia Aquifer System to the riverflows and the basement influence in the west portion, with likely leakage of aquifer groundwater.
Hydrogeological model of the Urucuia aquifer system in the rio Grande basin (Bahia, Brazil)
Keywords: Grande river; Numerical simulation; Urucuia aquifer system; Urucuia group